National radiotherapy dosimetry audit in the UK – A vision and roadmap - Sarah Misson; Antony L Palmer; Patricia Diez; Mohammed Hussein; Catharine H Clark (IPEM-Translation)
Radiotherapy dosimetry audit is an important element in the overall quality assurance of radiotherapy delivery and has become established as best practice prior to implementation of new equipment, techniques or clinical trials.The Institute of Physics and Engineering in Medicine (IPEM) Interdepartmental Dosimetry Audit group (IDA) facilitates regional audits across the UK through a network of 8 regional chairs. This is a well-established and successful network utilising local staff resources and dosimetry equipment from each region to conduct audits for new radiotherapy equipment, techniques and annual reference audits. All dosimeters used are traceable to the National Physical Laboratory's (NPL) primary standard.NPL and the National Radiotherapy Trials Quality Assurance Group (RTTQA) perform audits for new techniques and clinical trials in the UK. The IPEM IDA, NPL and RTTQA have a joint vision of a national audit network so that comprehensive audits can be offered to all UK centres and bring together all UK dosimetry audit data within a centralised database to facilitate coordinated national audits. This will also allow centres to access and review their data for anonymous benchmarking against other UK centres to support quality improvement.Increasing the frequency and complexity of national audits to reflect current clinical practice is often inhibited by the cost of purchasing appropriate equipment. IPEM have now funded two phantoms that will enable national audits of gynae brachytherapy and head and neck external beam treatments through 2024–25.The aim of this Position Paper is to provide an update on the activities of the IPEM IDA and present the future vision and roadmap for the three UK dosimetry audit groups.